Dynaflow ™ 48, a microfluidic chip solution for increasing throughput and data quality in patch-clamp-based drug screening - Granfeldt, Daniel; Johansson, Marie-Louise; Sinclair, Jon; Pihl, Johan; Karlsson, Mattias (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2006)
Ion channels are transm embrane proteins, found in virtually all cell types throughout the human body. Ion channels underlie neural communication, memory, behavior, every movement and heartbeat, and are as such prone to cause disease if malfunctioning. Therefore ion channels are very important targets in drug discovery. The gold standard technique for obtaining information on ion channel function with high information content and temporal resolution is patch-clamp. The technique measures the minute currents originating from the movement of ions across the cellular membrane, and enables determination of the potency and efficacy of a drug. However, patch-clamp suffers from serious throughput restrictions due to its laborious nature. To address the throughput problems we have developed a microfluidic chip containing 48 microchannels for an extremely rapid, sequential delivery of a large number of completely controlled solution environments to a lifted, patch-clamped cell. In this way, throughput is increased drastically compared to classical patch-clamp perfusion set-ups, with uncompromised data quality. The 48-microchannel chip has been used for the characterization of drugs affecting ligand-gated ion channels including agonists, antagonists and positive modulators with positive effects on both throughput and data quality.